Pengaruh Pupuk P dan Dosis Inokulum Rhizobium sp. terhadap Pembentukan Bintil Akar dan Pertumbuhan Mucuna bracteata - Putra, Heru Admadja; Himawan, Achmad; Rochmiyati, Sri Manu (AGROISTA : Jurnal Agroteknologi, 2024)
The purpose of this study is to ascertain the impact of the combination between the dosage of P fertilizer and the inoculum dose of Rhizobium sp. on M. bracteata plants' root nodule growth and creation, the effect of P fertilizer doses on M. bracteata plants' root nodule growth and creation and the effect of Rhizobium sp. inoculum doses, on M. bracteata plants' root nodule growth and creation. This research was carried out at KP2 of the STIPER Agricultural Institute which is located in Wedomartani Village, Depok District, Sleman Regency, DIY, with an altitude of 118 meters above sea level, from January to June 2024. This research was carried out using a two-factor experimental method prepared in RAL. The first factor is the dose of P fertilizer (TSP) consisting of 4 dose levels, namely: 0 g/polybag, 1 g/polybag, 2 g/polybag, and 3 g/polybag. The second factor is the dose of Rhizobium sp. inoculum which consists of 4 dosage levels, namely: 0 g/polybag, 5 g/polybag, 10 g/polybag, 15 g/polybag. These two variables were used to create 4 x 4 = 16 treatment combinations. Each treatment was then repeated four times, resulting in 16 x 4 = 64 experimental plants in terms of seeds. Analysis of variance (ANOVA) was used to assess the research data at the 5% significant level. The treatment that had a real effect in the DMRT follow-up test was at the 5% significant level. The results of the research showed that there was a real interaction between the treatment combination of P fertilizer dose and Rhizobium sp. inoculum dose on the parameters of fresh root weight, root length, number of ineffective root nodules, shoot dry weight and root dry weight. The combination of P fertilizer dose of 1 g/plant and Rhizobium inoculum 5 g/plant produces the best fresh root weight, the combination of P fertilizer dose of 0 g/plant and Rhizobium inoculum 10 g/plant produces the best root length, the combination of P fertilizer dose of 0 g/plant and Rhizobium inoculum 15 g/plant produced the least number of ineffective root nodules, the combination of P fertilizer dose 1 g/plant and Rhizobium inoculum 5 g/plant produced the best shoot dry weight, the combination dose of P fertilizer 1 g/plant and Rhizobium inoculum 5 g/ plants produce the best root dry weight. Providing P fertilizer doses of 0, 1, 2, and 3 g/plant had the same effect on the growth and formation of root nodules of M. bracteata plants. Giving Rhizobium sp. inoculum doses of 0, 5, 10, and 15 g/plant had the similar impact on M. bracteata plant development and nodule production.